PsycEXTRA Dataset 2004
DOI: 10.1037/e462852006-001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Logistics as a Force Multiplier: An Analysis of Reported Fatigue Factors From Southwest Asia Warfighters

Abstract: Approved for public release, distribution unlimited THIS PAGE INTENTIONALLY LEFT BLANK i REPORT DOCUMENTATION PAGE 12a. DISTRIBUTION / AVAILABILITY STATEMENTApproved for public release, distribution unlimited 12b. DISTRIBUTION CODE ABSTRACTThe purpose of this thesis is to analyze data related to sleep patterns of warfighters deployed to the Southwest Asia (SWA) Area of Operation.To this end, we collected subjective survey data from warfighters operating in Iraq and Kuwait from 25 August -15 October 2003 (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…Yet, this result is in keeping with results from other studies conducted in Southwest Asia, which reported sleep issues in U.S. Anny and Marine Aviation units (Doheney, 2004;Miller, Shattuck, & Matsangas, 2006). (For a review of fatigue in military operational environments, refer to Miller, Matsangas, & Shattuck, 2008.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Yet, this result is in keeping with results from other studies conducted in Southwest Asia, which reported sleep issues in U.S. Anny and Marine Aviation units (Doheney, 2004;Miller, Shattuck, & Matsangas, 2006). (For a review of fatigue in military operational environments, refer to Miller, Matsangas, & Shattuck, 2008.…”
Section: Discussionsupporting
confidence: 80%
“…The majority of participants in this survey were junior leaders (i.e., platoon leaders, company commanders, or staff officers at the company or battalion level): If they did not receive briefings on sleep management planning, it is likely they did not give such briefings to the soldiers for whom they were responsible. The findings from this survey indicate that this figure has dropped even lower than that reported by Doheney (2004), pointing to the possibility that commanders address sleep management issues even less now than at the beginning of the Global War on Terror. In many units, even the most basic sleep and fatigue management practices (e.g., encouraging napping or designating dark and quiet places to sleep) were not implemented.…”
Section: Discussioncontrasting
confidence: 40%
“…The available evidence indicates that military training and service do indeed tax sleep, and studies of sleep in modern military campaigns have found that disturbed sleep and sleep deprivation are relatively commonplace (Miller et al, 2011). The results of a survey of 273 American soldiers deployed during Operation Iraqi Freedom showed that sleep deprivation was a common occurrence (Doheney, 2004), and between 73% and 83% of the soldiers showed moderate symptoms of sleep deprivation, and 14% to 23% showed significant symptoms of sleep deprivation. That study concluded that the soldiers who had a plan for sleep and rest maintained better operational capability.…”
Section: Sleep and Performance In The Armed Forcesmentioning
confidence: 99%